Competitive weightlifting for children: The issue of safety - Pierce, K.; Byrd, R. (2001)
It is clear that the potential for injury is an issue that requires ongoing scientific study. However, anecdotal reports and conjecture regarding injury continue to limit early participation and possibly eventual potential for success. In conclusion, competitive weightlifting can be appropriate for children given supervision in training and competition by well-qualified professionals. For those with remaining doubts, a conservative approach could include scoring for technique rather than only total weight lifted or totaling multiple lifts rather than just the best of the two lifts. As with other sports, motivation would be minimal without some form of competition.